Cultural Adaptation and Validation of the Empathy Circle in Dementia Care for Older Adults - Tiago Teófilo; Valkenia Silva; Rafaella Veras; Jacira Oliveira; Wilson Abreu (Journal of Gerontological Nursing, 2026)
Purpose: To culturally adapt and evaluate the content validity of the Empathy Circle (EC) intervention for Brazilian dementia care settings. Method: The current methodological study was guided by the Planned Intervention Adaptation protocol. Adaptation and validation used a modified Delphi technique with expert panels ( n = 5: nursing, geriatrics, neurology, philosophy). Qualitative data from experts and participants were descriptively analyzed and organized according to the Delphi method. For pilot sessions, a directed content analysis was used, grouping responses into predefined units. Quantitative analysis included the content validity index (CVI) and Gwet's coefficient. Results: Qualitative analysis revealed a positive emotional effect and suggestions for improving the physical setting and session duration. The EC achieved a mean CVI of 96%, with strong expert agreement. Participants reported enhanced emotional support, empathy, and reflective practice. Conclusion: The EC showed cultural validity and potential as a psychosocial tool for promoting empathy in dementia care, with high acceptability and adaptability.